A Constitution without Constitutionalism: A Gambian Paradox - Mendy, Ousu (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
Constitutionalism and democratization are the current governance trends in Africa, and these are complemented with new constitutions. The Gambia is not an exception as it transcends from dictatorship. However, the country faces a paradoxical menace of a constitution without constitutionalism as it faces deficit of constitutionalism in praxis despite its theoretical deliberation in the State’s 1997 Constitution. This research uses doctrinal or normative legal research with focus on provisions of laws, books, journal articles and other secondary materials that speak to the facts in issue. This Africa’s smallest mainland country is a victim of the 1884 – 1885 Berlin Conference as it still tries to give much premium to foreign legal systems over customary practices of the people before this Berlin project. While constitutionalism seeks to limit the power of the government, its most critical constituent as regards the concept of constitution without constitutionalism is the rule of law. The rule of law premises on the ground that all state’s constituents must be subject to the law. Therefore, the metaphor of a saviour, savage, and victim as the 1997 Constitution, the State and freedom of expression respectively suggests the totality of the complexity of a constitution without constitutionalism.